AN ANALYSIS OF HYPERBOLE FOUND IN SHAWN MENDES SONG LYRICS - Amandus Yasmin; Ni Nyoman Deni Ariyaningsih; IGA Vina Widiadnya Putri (International Journal of English Learning and Applied Linguistics (IJELAL), 2021)
Language is the primary media to communicate, and it can build the relationship with each other which has function to carry the meaning. This study concerns to analyze hyperbole found in Shawn Mendes song lyrics that were released in 2016. There are two problems that are formulated in this study, they are: (1) what are hyperbole found in Shawn Mendes song lyrics; (2) what are the meaning of hyperbole found in Shawn Mendes song lyrics, there are two theories used in this research the first theory proposed by Knickerbocker and Reninger (1963:367) that is used to identify hyperbole and the second theory is the theory of meaning which supported by Leech (1981) to analyze the meaning. The method used in collecting the data was done by formal and informal method. The writer collected the data by listening the songs, reading the scripts, underling, and classifying the lyrics which are contain one type of figurative language that is hyperbole. The data analyzed descriptively by using qualitative method. The total of hyperbole found in eight tittle of Shawn Mendes lyrics are 10 terms, the songs that most appear used of hyperbole is “lights on” which has three terms.